Pengaruh Rasio Likuiditas, Solvabilitas, Profitabilitas, Dan Aktivitas Terhadap Pertumbuhan Laba Pada Perusahaan Logistik Dan Transportasi - Aisyah Suhendra; Aprilia Cahya Sekarningrum; Maliki Heru Sentosa (Program Studi Akuntansi Sekolah Tinggi Ilmu Ekonomi Tri Bhakti, 2022)
This study aims to determine the ratio of Liquidity, Solvency, Profitability, and Activity to Profit Growth. The population used in this study are Logistics and Transportation Companies listed on the Indonesia Stock Exchange in the 2018-2021 period. In this study using quantitative methods. The data analysis tool used in this research is SPSS 25 software, with classical assumption test, multiple linear regression analysis, hypothesis testing. The results of this study partially show that the Liquidity Ratio, Solvency Ratio, and Activity Ratio have no significant effect on profit growth, while the Profitability Ratio has a significant effect on profit growth. Simultaneously the Liquidity Ratio, Solvency Ratio, Profitability Ratio and Activity Ratio have a significant effect on profit growth.